2008
DOI: 10.1016/j.jsb.2007.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the E2 ligase fold: Implications for enzymology and evolution of ubiquitin/Ub-like protein conjugation

Abstract: The configuration of the active site of E2 ligases, central enzymes in the ubiquitin/ubiquitin-like protein (Ub/Ubl) conjugation systems, has long puzzled researchers. Taking advantage of the wealth of newly available structures and sequences of E2s from diverse organisms, we performed a largescale comparative analysis of these proteins. As a result we identified a previously under-appreciated diversity in the active site of these enzymes, in particular, the spatial location of the catalytic cysteine and a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(122 citation statements)
references
References 57 publications
2
120
0
Order By: Relevance
“…1 B and C) (22)(23)(24). This fold was also related to those of the RWD (RING finger-, WD-repeat-, and DEAD-like proteins) domain and ubiquitin-conjugating enzymes (25,26). The fold similarity between Mad1 CTD and the CTDs of Spc25 and Csm1 was unexpected, as they share no obvious sequence similarity.…”
Section: Resultsmentioning
confidence: 96%
“…1 B and C) (22)(23)(24). This fold was also related to those of the RWD (RING finger-, WD-repeat-, and DEAD-like proteins) domain and ubiquitin-conjugating enzymes (25,26). The fold similarity between Mad1 CTD and the CTDs of Spc25 and Csm1 was unexpected, as they share no obvious sequence similarity.…”
Section: Resultsmentioning
confidence: 96%
“…rFcUbc may enter hemocytes via endocytosis, since it has been reported that recombinant immulectin-3 (IML-3), a C-type lectin from an insect, Manduca sexta, can be translocated from hemolymph into hemocytes (35), a result consistent with ours. It has been reported that the conserved cysteine residue in E2 is involved in the formation of a covalent bond with ubiquitin (1,18,21,32,34). In FcUbc, this conserved Cys is Cys-86, and a mutant FcUbc protein (mFcUbc) in which Cys-86 was mutated to Ser was also expressed and purified.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study addressing the activation of ubiquitin by specific E1-and E2-enzymes, 29 E2s accepted ubiquitin from UBE1 and UBA6 of which 14 were charged by UBE1 (but not by UBA6), 9 were charged by both UBE1 and UBA6 and 1 by UBA6 (but not UBE1), thus highlighting that each E1 has a distinct preference for a specific E2 49 . Within the E2, it is the UBC domain that is of particular importance as it is responsible for specific binding to the relevant E3-ligase 55 Structurally, UBC domains consists of α-helices, β-sheets and variable loop regions that surround an active-site catalytic domain 55 . Amino (N-Ex, N-) and Carboxyl (C-Ex, C-) terminal extensions have also been discovered to flank the catalytic domain ( Figure 2) and shown to be important in steps such as substrate selection, subcellular localisation and dimerisation.…”
Section: E2 Conjugating Enzymesmentioning
confidence: 99%